CYTOTOXICITY OF METABOLITES PRODUCED BY ENDOPHYTIC FUNGUS CLADOSPORIUM SP. ISOLATED FROM MARINE MACROALGAE ON INÂVITRO MCFÂ7, HELA, AND DU-145 CELL LINES - Wulandari, Asri Peni; Examinati, R. R. Indry Noviarin; ., Madihah; Huspa, Desi Harneti Putri; Andayaningsih, Poniah; Andayaningsih, Poniah (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: To investigate the in vitro cytotoxicity effect of the crude ethyl acetate extract of Cladosporium sp. on MCF-7, HeLa, and DU-145 cell lines. Methods: In vitro cytotoxicity was evaluated by tetrazolium reduction assay. The percentage of cell inhibition was analyzed using probit analysis to obtain 50% inhibitory concentration (IC50). Morphological alteration of the cell lines after exposure with extract was observed under an inverted microscope. Results: The ethyl acetate extract of the metabolite performed an anticancer activity for cancer cell line MCF-7, HeLa, and DU-145 with IC50 respectively 8.46 Î¼g/ml; 9.87 Î¼g/ml; and 98.03 Î¼g/ml. The extract shows greater the anticancer activity and has strong antiproliferative on MCF-7 and HeLa cell line than DU-145. Confirmation morphological were observed under the inverted microscope showed a morphological change in cancer cells when incubated with the extract. Conclusion: From the performed assay, the crude extract of Cladosporium sp. exhibit cytotoxic activity against MCF-7, HeLA, and DU-145.